Augmented reality as a pedagogical resource for elementary school teachers in the early years of education - Borborema, Silvana M. T.; Maurício, Claudio R. M. (Companion Proceedings of the Symposium on Virtual and Augmented Reality (SVR); 2024: Companion Proceedings of the 26th Symposium on Virtual and Augmented Reality, 2024)
In Education 4.0, augmented reality emerges as an alternative to mediate teaching. This research aimed to contribute to the development of digital competence of elementary school teachers by promoting the use of augmented reality as a pedagogical resource. The methodology adopted, Applied, exploratory, and descriptive approach, using case study and action research techniques. Data were collected through questionnaire and participant observation. The result showed positive perceptions about augmented reality technology, but the lack of mobile devices was identified as the main limitation for its implementation.